Analysis of radiative transfer in a turbulent sooting jet flame using a Monte Carlo method coupled to large eddy simulation. (September 2019) - Rodrigues, Pedro; Gicquel, Olivier; Franzelli, Benedetta; Darabiha, Nasser; Vicquelin, Ronan
Highlights: Coupled Monte Carlo - Large Eddy Simulation with a soot sectional model and spectral properties of soot particles and burnt gases. Application to a turbulent and sooting jet flame with comparison to measurements. Analysis of radiative heat transfer from the validated simulation results to study the impact of soot particles. Assessment and modelling of turbulence-radiation interactions captured by the simulation for both gaseous and soot contributions. Abstract: Due to the relevant contribution of radiative transfer in the global energy balance of many industrial combustion systems, a deep understanding and accurate modelling of gas and soot radiative transfer is necessary. This topic is addressed here numerically in a canonical turbulent sooting configuration, i.e. an ethylene-air jet diffusion flame. The study is based on a coupled Monte Carlo - Large Eddy Simulation. In order to introduce as much physical details as possible, a recently-developed sectional model is used for soot particles description and the radiative transfer equation is solved using a Monte-Carlo method. A cK model describes gas radiative properties and the Rayleigh's theory is considered for soot particles properties. Numerical results are compared to experimental data on radiative intensity measured along the flame height to validate the proposed methodology. Then, the different radiative contributions i.e. emission-absorption, gas-soot, are analyzed to study the nature of the radiative heat transfer in the investigated flame. Finally, turbulence-radiation interactions are quantified for the total mean emitted, absorbed and radiative powers. Closure of these effects on the mean emitted power is proposed and discussed. Opposite effects of turbulence-radiation interactions are observed for the gaseous and the soot contributions: the increase in mean emitted power for the gaseous phase is due to temperature fluctuations whereas a decrease of the solid phase contribution appears from a negative temperature-soot volume fraction correlation.